ANALISIS KESALAHAN SISWA SMA DALAM MENYELESAIKAN SOAL HOTS BERDASARKAN NEWMAN’S ERROR ANALYSIS (NEA) - Rizky Ananda; Harry Aprianto Barus Barus; Anggi Wandii; Putri Aprilisia Simbolon Simbolon; Ade Andriani (Universitas Teknokrat Indonesia, 2026)
This study aims to analyze students' errors in solving Higher Order Thinking Skills (HOTS)-based composite function problems using Newman’s Error Analysis (NEA). This research employed a descriptive qualitative approach with 26 eleventh-grade students at SMA Negeri 1 Percut Sei Tuan as the research subjects. The instruments used consisted of four validated essay questions and interview guidelines to support data analysis. The data analysis technique was carried out through the stages of data reduction, data presentation, and conclusion drawing. The results indicate that students made errors across all stages of NEA, namely reading, comprehension, transformation, process skills, and encoding. The percentage of errors shows that process skill errors are the most dominant (34.61%), followed by encoding errors (29.81%), while transformation errors have the lowest percentage (8.65%). Comprehension and reading errors are categorized as low (11.54%) to moderate (13.46%), yet they still influence subsequent stages. These findings indicate that students' errors are systemic and related to weaknesses in procedural aspects as well as mathematical communication. Therefore, instructional efforts are needed that specifically emphasize reinforcement and scaffolding at the process skill and encoding stages through structured procedural exercises and continuous practice in presenting final answers accurately in accordance with the problem context.